PENGEMBANGAN SIMATREN (SISTEM INFORMASI PESANTREN) DALAM MENGELOLAH MANAJEMEN INTERNAL PESANTREN DI PP RAUDHATUL ULUM 1 GANJARAN-MALANG - Abdurohim; Nikmahtul Khoir Tri Yulia (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2023)
The development of Islamic boarding schools needs attention in improving the quality of management of facilities and infrastructure in line with technological developments. This Islamic boarding school has made changes in rearranging management and data collection in a modern way in the digitalization era. The aim is to develop the quality of website-based simatren as one of the manifestations of developing facilities within Islamic boarding schools. Researchers who use the Research & Development (R&D) methodology with a mixed method approach. The results of the data to be analyzed from the form of input, output, and outcome. Research results include input, substance organization and knowing the lack of features in repairing data through a system that has managed each substance. Output, the data that is managed begins to be organized, the students access it via the FRID Card automatically. The form of evaluation as reporting and follow-up of data can be seen more clearly and measurably. The quality competence of members as users seems to be getting used to the simatren in supporting soft skills and hard skills even though it is still in the transitional stage (trial and error). Outcome, the training process as a strengthening of management life skills by observing its development includes A yielding a percentage of 57%, while B yielding a percentage of 73.3%. This study concluded that simatren is a form of appropriate infrastructure in overcoming problems related to management and data collection in regulating quality management in a clear and sequential manner.